How smart is the strategy of investing in 52–week high hitting stocks with past positive net profit in Indian market?. (23rd February 2015) - Sharma, Amita; Mehra, Aparna
We aim to investigate if the stocks recently hitting their 52–week high points along with consistent performance in past few quarters offer attractive opportunities in building a portfolio. We first identify the stocks hitting their 52–week high points, their prices have not fallen below 30% of their peak positions along with the criterion of last four quarters positive net profit. These stocks are called the 'filtered stocks'. The 12 years period of study from April 2001–December 2012 on CNX–200 index shows that the filtered stocks generally do not outperform the remaining stocks in return earnings except when the future period is 'bearish'. Next, we construct optimal portfolios from the filtered stocks and the remaining stocks. The optimal portfolios from the former are able to produce positive returns on many instances of bearish periods, while the same is not true for the optimal portfolios from the remaining stocks and CNX–200.